2016
DOI: 10.2134/agronj2015.0425
|View full text |Cite
|
Sign up to set email alerts
|

Heterotic Patterns of IITA and CIMMYT Early‐Maturing Yellow Maize Inbreds under Contrasting Environments

Abstract: Drought and low soil nitrogen (low-N) constitute major constraints to maize (Zea mays L.) production in West Africa (WA). Th e International Institute of Tropical Agriculture (IITA) and International Center for Maize and Wheat Improvement (CIMMYT) have developed drought and low-N tolerant inbreds for Africa. Combinations between selected IITA and CIMMYT inbreds could produce outstanding hybrids. Diallel crosses of 12 IITA and fi ve CIMMYT early yellow inbreds plus four checks were evaluated under drought, low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 59 publications
4
26
1
Order By: Relevance
“…Generation mean analysis is useful in determining gene effects for polygenic traits (Mather & Jinks, ) by allowing the computation of digenic genetic effects such as additive × additive [ i ], additive × dominance [ j ] and dominance × dominance [ l ] interactions (Singh & Singh, ). The preponderance of additive gene action over dominance gene action for grain yield and Striga traits has been documented in maize (Akaogu et al., ; Badu‐Apraku et al, ,). Partitioning of the genetic effects into its components including additive, dominance gene effects ( d and h ) and the three types of digenic gene actions, that is, additive × additive ( i ), additive × dominance ( j ) and dominance × dominance ( l ) effects will provide invaluable information for planning an efficient gene deployment schemes in Striga resistance enhancement programmes of SSA.…”
Section: Introductionmentioning
confidence: 99%
“…Generation mean analysis is useful in determining gene effects for polygenic traits (Mather & Jinks, ) by allowing the computation of digenic genetic effects such as additive × additive [ i ], additive × dominance [ j ] and dominance × dominance [ l ] interactions (Singh & Singh, ). The preponderance of additive gene action over dominance gene action for grain yield and Striga traits has been documented in maize (Akaogu et al., ; Badu‐Apraku et al, ,). Partitioning of the genetic effects into its components including additive, dominance gene effects ( d and h ) and the three types of digenic gene actions, that is, additive × additive ( i ), additive × dominance ( j ) and dominance × dominance ( l ) effects will provide invaluable information for planning an efficient gene deployment schemes in Striga resistance enhancement programmes of SSA.…”
Section: Introductionmentioning
confidence: 99%
“…and International Maize and Wheat Improvement Centre (CIMMYT) researchers, along with their national programs collaborators are now developing low-N (about 30 kg N) tolerant maize germplasm. Studies by Badu-Apraku et al, showed that, in addition to being low-N tolerant, the resulting germplasm had the value addition of being high yielding at a high level of N, usually 90 kg ha -1 [4,33]. The present study was the first attempt at evaluating such material at N rates higher than 90 kg ha -1 .…”
Section: Discussionmentioning
confidence: 76%
“…Following combining ability studies involving inbreds from IITA and CIMMYT, some CIMMYT lines were identified to have potentials for improving IITA's early maturing and intermediate maturing germplasms for drought and low nitrogen tolerance (Adebayo et al, 2013;Ifie et al, 2015;Badu Apraku et al, 2016). However, limited studies have been conducted to examine the potentials of adapted and exotic non-borer maize inbred lines for their direct use in hybrid combinations aimed at stem borer resistance efforts.…”
Section: Introductionmentioning
confidence: 99%